The impact of paramedic shift work on the family system: a literature review. (2nd August 2019) - Anderson, Lucy
Abstract : Aim: The current review investigates the impacts of paramedic work on the family system. Paramedics are taking time off or leaving through stress, and career decisions could be influenced by this perceived impact. Method: A systematic literature review was conducted and the literature critiqued. Two themes were identified: emotional labour and work-family fit. Results: Paramedics rely on families for emotional support, putting them at risk of vicarious trauma. The historical male coping culture of paramedic practice deters processing at work, detrimentally carrying this processing into the home environment. Additionally, several shift characteristics contribute to work-family conflict, child-rearing conflict and difficulties maintaining a social life. Conclusions: Key organisational culture change is needed from denigrating staff for showing emotions and struggling to find work-life balance, to one that improves experiences at work and therefore at home as well. Recent movement towards almost equal gender balance may present a particular opportunity to deliver culture change. Further research is required to better understand the impact that shift work has on the family.